Spinoza's radical theology : the metaphysics of the infinite - Huenemann, Charles; Cambridge eBooks (Durham : Acumen Publishing, 2014)
The advent of modern science brought deep challenges to traditional religion. Miracles, prophecy, immortal souls, absolute morality; all of these fundamental notions were challenged by the increasingly analytical and skeptical approach of modern scientists. One philosopher, Baruch Spinoza, proposed a new theology, rooted in a close analysis of the Bible, which could fit this new science and provide a sound basis for a social order. Spinoza's Radical Theology explains the mechanics and meaning of Spinoza's ideas and how they can inform the questions with which we still struggle today.
Introduction: Spinoza's theological project -- Reading scripture rightly -- God, as known by reason -- The genesis of all things -- Our place in the world -- Spinoza's republic -- Conclusion: Spinoza vs Nietzsche.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Philosophical theology -- History -- 17th century; Rationalism -- History -- 17th century; Electronic books